Navigating healthcare in higher education for students with gynaecological pain: an exploratory survey - Katie Paddock-Hall (BMC Women's Health)
Abstract Background University students face unique challenges in accessing healthcare, particularly women who experience painful gynaecological conditions. These conditions can impact their quality of life and educational engagement. Gynaecological pain is frequently misattributed as ‘normal’ dysmenorrhea, leading to delays in seeking medical advice and diagnosis. Research on how women with gynaecological conditions navigate healthcare is lacking in a UK higher education context. This study aims to explore university students’ experiences of gynaecological pain within higher education, and how they navigate healthcare. Methods A web-based questionnaire integrating quantitative and qualitative items distributed to university students in England. The survey included the Menstrual Symptoms Index (MSI) to assess the severity and frequency of symptoms. Questions explored experience of accessing healthcare for gynaecological pain and the impact of symptoms on aspects of daily life and educational engagement. This project was supported by an advisory group comprising relevant stakeholders. Results The study included 70 university students, predominantly aged 18–24. Gynaecological pain was highly prevalent, but 52% of participants had not spoken to a healthcare professional about this, 56% were not taking pain medication, and 80% had not sought university support. This was most typically due to normalisation of symptoms. Some participants had difficulties accessing healthcare around university commitments. Many reported negative experiences with healthcare professionals who dismissed or minimised their pain, particularly among younger participants. This pain impacted educational engagement with participants reporting difficulties in concentrating, attending classes, and completing assignments. Participants felt supported by individual university tutors but experienced difficulties navigating the procedural landscape of university to access accommodations. Students would benefit from greater awareness of the impact of gynaecological conditions among academic and healthcare professions. Conclusions Gynaecological pain has a significant impact on university students’ educational engagement. There is a need for better support systems within universities, including improved awareness and understanding of gynaecological pain among staff and flexible academic policies. Training for healthcare providers to recognise and validate gynaecological pain is also essential. Addressing these issues can improve the quality of life for students and enhance their participation in educational settings.